2017
DOI: 10.1111/tme.12405
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E: the current state of play

Abstract: The hepatitis E virus (HEV) is a major cause of acute hepatitis globally. Genotypes 1 and 2 (G1 and G2) are obligate human pathogens transmitted faeco-orally, leading to epidemics in developing countries. In contrast, genotypes 3 and 4 (G3 and G4) have a wider host range, including humans, but are primarily porcine viruses and are transmitted from animals to humans as a food-borne zoonosis when meat from an infected animal is consumed. HEV is increasingly recognised as a problem in developed countries, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 104 publications
1
47
0
1
Order By: Relevance
“…In many European countries similarly high seroprevalence differences have been recorded; for example, 25%–86.4% in France and 21%–27% in the Netherlands [19,20,27,28]. Interestingly, the French Jura, a region directly adjacent to the west of Switzerland, has reported a similar seroprevalence to the one in our report [20].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In many European countries similarly high seroprevalence differences have been recorded; for example, 25%–86.4% in France and 21%–27% in the Netherlands [19,20,27,28]. Interestingly, the French Jura, a region directly adjacent to the west of Switzerland, has reported a similar seroprevalence to the one in our report [20].…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested that these large regional variations may be a consequence of the consumption of a regional delicacy of traditional raw dry-cured pork sausage containing raw pork liver (e.g. mortadella di fegato crudo ) [19,31]. It remains to be seen whether the variation in Switzerland can be explained by these dietary differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic liver diseases include hepatitis caused by the hepatitis B virus (HBV), hepatitis C virus (HCV), alcohol, autoimmune, fat, all of which can progress to cirrhosis, and various factors involving genetic background, hormones, environmental agents, drugs, and viral co‐infection have been proposed as triggers for the histological development . Hepatitis E virus (HEV) infection has been suggested as one of the contributing factors . The viral hepatitis caused by HEV infection is generally considered to be a self‐limiting acute course and the majority of the patients are healed within 6 weeks after onset .…”
Section: Introductionmentioning
confidence: 99%
“…In several countries, inadvertent HEV transmission to blood recipients was associated with blood donation from healthy donors who may have acquired zoonotic foodborne HEV infection . Reports of such blood‐borne HEV transmission has increased the awareness of potential risks from HEV in donated blood and blood components.…”
mentioning
confidence: 99%